CHARACTERISTICS OF BIOLOGICAL PROPERTIES OF ETIOLOGICAL AGENTS OF ACUTE BACTERIAL CONJUNCTIVITIS (Eurasian Journal of Medical and Natural Sciences, 2026)
During the study, algorithms for microbiological and mycological analysis of bacterial conjunctivitis in adults were developed based on the obtained microbiological test results. Their advantage lies in the ability to plan microbiological and mycological tests, implement the process step by step, and provide timely and reliable reporting of test results. The proposed algorithms for microbiological and mycological analysis are recommended for the first time for microbiological confirmation of the diagnosis of bacterial conjunctivitis and are convenient for laboratory testing.